(untitled) (Research, Society and Development, 2021)
C3 plants tend to present more evident responses in their growth when there is an increase in CO2 in the environment. Such observations are not so evident in plants with C4 metabolism, which are considered more naturally evolved due to their functional anatomy, which is capable of concentrating a greater amount of CO2 in their cells, making photosynthesis a more efficient process. Several studies are found that suggest greater growth of plants that use both C3 and C4 metabolism when subjected to higher CO2 concentrations than current environmental conditions. The objective of the present work was to carry out a review of the influence of atmospheric CO2 concentration on the growth of cultivated plants with emphasis on the cultivation of beans and corn and weeds. The increase in carbon dioxide benefits the growth of both C3 metabolism and C4 metabolism plants. Knowing that the future trend is that the concentration of carbon dioxide is increased in the atmosphere, due to emissions mainly from fossil fuels, it will become appropriate to invest in more inputs and technologies to reduce competition with weeds, as their growth also it will be favored and may interfere with competition for nutrients, and thus reduce crop productivity.